PENGENDALIAN WAKTU PELAKSANAAN PROJECT DENGAN MENGGUNAKAN EARNED VALUE CONCEPT - Felix Setiawan; Maulana Ihsan (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2023)
The success of a project is a series of activities that include the stages of planning, implementation and supervision, so that the goals that have been set can be achieved and implemented. Therefore, it is necessary to carry out supervision and control measures in various sectors, especially time control. The method used in this study is the Earn Value Concept method. This research was conducted, with the aim of knowing the performance of the project, problems occurring and solutions to these problems. The data used are in the form of an S curve, RAB, and weekly progress reports. From these data obtained the results of BCWS and BCWP, with the help of Microsoft Excel programs set SV, SPI values, as well as predicting the final time of the project (ETC and EAC).